Expectation Management in Mergers and Acquisitions - He, Jie (Jack); Liu, Tingting; Netter, Jeffry; Shu, Tao (Management Science, 2020)
Takeover bidders in stock-for-stock mergers have strong incentives to increase their own premerger stock prices to lower their acquisition costs. We find that before announcements of stock mergers, bidders manage down analyst earnings forecasts prior to earnings releases. Such expectation management benefits bidders by increasing their own stock prices and saving on acquisition costs. Additionally, analysts who have close relations with stock bidders are more likely to participate in expectation management. For identification, we use an instrumental variable analysis, a pseudo-event analysis, and a propensity score-matching approach. Our paper provides evidence on expectation management as a previously underexplored opportunistic behavior by takeover bidders. This paper was accepted by Shivaram Rajgopal, accounting.